Antibiotic Resistance in Wastewater Treatment Plants and Transmission Risks for Employees and Residents: The Concept of the AWARE Study - Laura Wengenroth; Fanny Berglund; Hetty Blaak; Mariana Carmen Chifiriuc; Carl-Fredrik Flach; Gratiela Gradisteanu Pircalabioru; D. G. Joakim Larsson; Luminita Marutescu; Mark W. J. van Passel; Marcela Popa; Katja Radon; Ana Maria de Roda Husman; et al. (MDPI AG, 2021)
Antibiotic resistance has become a serious global health threat. Wastewater treatment plants may become unintentional collection points for bacteria resistant to antimicrobials. Little is known about the transmission of antibiotic resistance from wastewater treatment plants to humans, most importantly to wastewater treatment plant workers and residents living in the vicinity. We aim to deliver precise information about the methods used in the AWARE (Antibiotic Resistance in Wastewater: Transmission Risks for Employees and Residents around Wastewater Treatment Plants) study. Within the AWARE study, we gathered data on the prevalence of two antibiotic resistance phenotypes, ESBL-producing E. coli and carbapenemase-producing Enterobacteriaceae, as well as on their corresponding antibiotic resistance genes isolated from air, water, and sewage samples taken from inside and outside of different wastewater treatment plants in Germany, the Netherlands, and Romania. Additionally, we analysed stool samples of wastewater treatment plant workers, nearby residents, and members of a comparison group living ≥1000 m away from the closest WWTP. To our knowledge, this is the first study investigating the potential spread of ESBL-producing E. coli, carbapenemase-producing Enterobacteriaceae, and antibiotic resistance genes from WWTPs to workers, the environment, and nearby residents. Quantifying the contribution of different wastewater treatment processes to the removal efficiency of ESBL-producing E. coli, carbapenemase-producing Enterobacteriaceae, and antibiotic resistance genes will provide us with evidence-based support for possible mitigation strategies.